The Didactic Potential of University Electronic Information and Educational Environment in the Context of a Pandemic - Kostikova, Natalia Anatolyevna (2020)
The article outlines the possibilities of using a University Electronic Information-Educational Environment (EIEE) that facilitates the University educational process in the context of a pandemic considering the variety of applicable e-learning tools and difficulties encountered by teachers and students in organizing and implementing distance learning within this period. The major objective of the article is revealing the didactic potential and technologies for providing remote access to University educational resources for arranging the educational process. Study results. The study identified E-resources and electronic environment activities that found to be the most popular between educational process participants in the period of forced transition to distance learning. Besides, the authors list the main difficulties in distance learning arrangement and suggested ways in their overcoming aided by EIEE didactic possibilities and potential. The principal research methods are questionnaire survey, expert assessment method and statistical processing of quantitative research results. The practical implications of the study comprise recommendations development for distance learning arrangement providing for modifying various components of students’ training system in higher education institutions, which is especially important not only in the context of a pandemic, but also under standard academic situations. The paper sets the direction of further research in upgrading the education system. The materials of the article can be helpful to teachers of higher educational institutions, further education establishments, to heads of educational institutions and school teachers in resolving the issues of organizing educational activities in the context of a pandemic for successful fulfillment of the basic educational programs.